Program Coping Mechanism untuk Mengelola Stres Akademik Siswa di Masa Pandemi COVID-19 - Lembang, Galdies Betsi; Huwae, Arthur; Siregar, Rotua M (Fakultas Psikologi Universitas Pancasila, 2022)
The COVID-19 pandemic appears to have spread and is having an impact on educational institutions' learning processes, as well as producing numerous psychological pressures that are detrimental to students' academic welfare. Students are subjected to continuous stress, which, if not addressed promptly and correctly, can lead to worsening and potentially dangerous problems. Therefore, the coping mechanism program is thought to be capable of assisting students in developing and executing optimal stress management methods in all academic activities. From January to May 2021, students from Barana Toraja Utara Christian High School class X-XII participated in community service activities (PkM). The exercise took the form of coping mechanism training . The results of the activity imply that students can use academic activities to develop coping skills in order to reduce stress and increase excitement and aggression in studying.